Web data management - Abiteboul, Serge (Cambridge University Press, 2012)
"The Internet and World Wide Web have revolutionized access to information. Users now store information across multiple platforms from personal computers, to smartphones, to Web sites such as YouTube and Picasa. As a consequence, data management concepts, methods, and techniques are increasingly focused on distribution concerns. That information largely resides in the network, as do the tools that process this information. This book explains the foundations of XML, the Web standard for data management, with a focus on data distribution. It covers the many facets of distributed data management on the Web, such as description logics, that are already emerging in today's data integration applications and herald tomorrow's semantic Web. It also introduces the machinery used to manipulate the unprecedented amount of data collected on the Web. Several "Putting into Practice" chapters describe detailed practical applications of the technologies and techniques. Striking a balance between the conceptual and the practical, the book will serve as an introduction to the new, global, information systems for Web professionals as well as for master's level courses"--